1991
DOI: 10.1002/art.1780340815
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalinase: A physiologic neuroimmunomodulator detected in the synovial fluid

Abstract: Enkephalinase (endopeptidase 24.11) is a metallopeptidase that is able to cleave not only neuropeptides and hormones but also immune mediators. The enzyme was quantified in synovial fluid obtained from 36 swollen joints. Its concentration correlated with the synovial fluid cell count, mainly the polymorphonuclear cells and lymphocytes, and with the erythrocyte sedimentation rate. No statistically significant difference in enkephalinase levels was demonstrated between the groups of patients with rheumatoid arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In addition, the recent demonstration ofmeasurable NEP-24. 1 1 activity in synovial fluids (55) suggests that the synovial fibroblast, in addition to expressing NEP-24. 11 on its cell surface, may also have the capacity to secrete this enzyme into the joint cavity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the recent demonstration ofmeasurable NEP-24. 1 1 activity in synovial fluids (55) suggests that the synovial fibroblast, in addition to expressing NEP-24. 11 on its cell surface, may also have the capacity to secrete this enzyme into the joint cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the enzyme has also been reported in human neutrophils [7] where it may play a role in the regulation of inflammation and chemotaxis [8]. A soluble form of NEP has been found in human plasma, cerebrospinal fluid and amniotic fluid [9], and this activity has been reported to increase during inflammatory processes in the synovial fluid [10] and in the serum of patients with sarcoidosis [11] or with adult respiratory distress syndrome (ARDS) [12]. NEP was also reported to increase in the serum of patients with endstage renal failure [13], and its enhancement in urine seems to be a marker of proximal tubular injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…This may result from either inhibition of their synthesis, or elevation of endopeptidase activity [7], as was demonstrated earlier in experiments with chronic administration of morphine [11]. On the other hand, it has been found that endopeptidase 24.11 can act as an immunomodulator [5] and its activation evidently not only accelerates proteolysis of opioids but also stimulates production of AMAB. Given the fact that AMAB bind with morphine more effectively than do morphine receptors [15], it may be assumed that stimulation of AMAB production is a key component in the formation of morphine resistance and tolerance.…”
Section: Resultsmentioning
confidence: 87%